Towards a Fuzzy Questionnaire of Felder and Soloman for determining learning styles without dichotomic in the answers - Silva Sprock, Antonio (Journal of Learning Styles, 2020)
The article shows the development and evaluation of the Learning Styles Fuzzy Questionnaire - FuzzyILS, based on the Felder and Silverman Learning Style Model and as an alternative fuzzy to the ILS Questionnaire created by Felder and Soloman. The FuzzyILS was created as an alternative to the limitation described by students who answered the ILS Questionnaire in previous research and they indicated that the dichotomy of the answers limited them to express their answers. The FuzzyILS has 5 options for each question then we calculate the degrees of membership in the fuzzy sets of the dimensions. Finally, the work shows the FuzzyILS evaluation, carried out in three phases, the first with 132 people in 5 universities in Venezuela and Brazil, the second evaluation with 180 students from the Central University of Venezuela and the third an internal consistency evaluation based on the Cronbach's alpha value.
Keywords: Felder & Soloman Questionnaire; Learning Styles; Felder and Silverman Learning Styles Model; Fuzzy Logic